Zn0.4Mg0.6Fe2O4 nanoenzyme: a novel chemo-sensitizer for the chemotherapy treatment of oral squamous cell carcinoma. Issue 3 (16th January 2023) - Chen, Liang; Kong, Qingmei; Tian, Mingxing; Zhang, Qian; Xia, Chengwan; Deng, Chao
Abstract : Zn0.4 Mg0.6 Fe2 O4 could serve as a promising novel chemo-sensitizer in the treatment of OSCC. Abstract : Hypoxic and acidic environments are the two main components of the microenvironment contributing to the poor efficacy of chemotherapy drugs in the treatment of oral squamous cell carcinoma (OSCC). In this study, we synthesized a series of Zn1– x Mg x Fe2 O4 nanomaterials with enzyme-like properties, including catalase (CAT)-like, peroxidase (POD)-like, and glutathione (GSH)-like activity in an acidic environment. Among them, Zn0.4 Mg0.6 Fe2 O4 performed the best and effectively increased the efficacy of doxorubicin (DOX) chemotherapy for the treatment of OSCC with reduced cardiotoxicity. Therefore, Zn0.4 Mg0.6 Fe2 O4 could serve as a novel chemosensitizer in the treatment of OSCC.